Lead-free environmental protection type 5G communication filter conductive silver paste
Patent Information
- Application Number
- CN202611478099.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明要解决的技术问题是:现有5G陶瓷滤波器用导电银浆多侧重导电性、附着力、热膨胀匹配或面浆、孔浆通用性改进,尚难以针对端面、侧壁、转角、凹槽及通孔边缘等异形金属化区域同时兼顾剪切填充、驻留锁形和烧结连续导通,仍易出现侧壁流挂、转角银层变薄、凹槽填充不足及局部导电连续性下降的问题,为此我们提出一种无铅环保型5G通信用滤波器导电银浆
[0038]本发明中,针对5G通信用陶瓷滤波器端面、侧壁、转角、凹槽及通孔边缘等异形金属化区域的成膜需求,将片状银粉、球形银粉和细粒径银粉构成三级银粉体系,并配合低流动界面结合型无铅玻璃粉及快恢复驻留锁形载体使用;片状银粉有利于在端面、侧壁及转角表面形成面内搭接导电结构,球形银粉有利于构建烧结导电骨架,细粒径银粉能够补偿转角内侧、凹槽底部及通孔边缘处的局部间隙;同时,快恢复驻留锁形载体使银浆在刮刀、网版或移印剪切作用下能够铺展进入异形区域,脱离剪切后又能够较快恢复支撑状态,从而减少侧壁流挂、边缘收缩、转角银层变薄和凹槽填充不足的问题,使湿银层在异形金属化区域具有较好的驻留稳定性和成膜均匀性。
Smart Images

Figure CN122991713A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic functional materials technology, and in particular to a lead-free, environmentally friendly conductive silver paste for 5G communication filters. Background Technology
[0002] Ceramic filters for 5G communication typically require the formation of a metallized silver layer on the surface of a ceramic substrate to achieve functions such as electrical signal transmission, grounding shielding, and subsequent welding connections. Conductive silver paste, a key material in the metallization process of ceramic filters, is generally composed of silver powder, glass powder, organic carriers, and additives. After printing, drying, and sintering, it forms a conductive silver layer on the surface of the ceramic substrate. As 5G communication filters develop towards miniaturization and high integration, their metallization areas are no longer limited to flat end faces but often involve irregularly shaped areas such as sidewalls, corners, grooves, steps, and through-hole edges. These areas involve continuous processes such as shearing and spreading, retention and shaping, drying shrinkage, and sintering during silver paste application, placing higher demands on the rheological recovery, film stability, conductivity continuity, and interfacial bonding stability of the silver paste.
[0003] Existing conductive silver pastes for 5G ceramic filters primarily focus on improving properties such as conductivity, adhesion, thermal expansion matching, or versatility for surface pastes and pore pastes. They pay insufficient attention to the comprehensive stability of silver pastes in irregularly shaped metallized regions during continuous processes such as shear spreading, retention and shaping, drying shrinkage, and sintering for conduction. For example, Chinese patent application CN112037960A discloses a conductive silver paste, its preparation method, and a 5G ceramic filter. This improves the thermal expansion coefficient matching, conductivity, adhesion, and thermal shock resistance of the conductive silver paste with the 5G ceramic filter substrate through the combination of silver powder, glass powder, organic carrier, and specific inorganic additives. Another example is Chinese patent application CN114520064A, which discloses a silver paste applicable to both surface pastes and pore pastes for 5G ceramic filters, its preparation, and application. This paste uses a blend of coarse, medium, and fine silver powder particles, along with a diluent to adjust the solid content and flowability of the silver paste, to meet the general requirements of both surface pastes and pore pastes. While the aforementioned technologies can improve the basic performance of silver paste for 5G ceramic filters from different perspectives, there is still room for further improvement in the adaptability of continuous film formation in irregularly shaped metallized areas such as end faces, side walls, corners, grooves, and through-hole edges. In particular, it is still difficult to fully balance the coordinated control of shear filling, residence lock-in, and sintering continuous conduction, thereby affecting the thickness uniformity and local conductivity continuity of the silver layer in irregularly shaped metallized areas. Summary of the Invention
[0004] The technical problem this invention aims to solve is that existing conductive silver pastes for 5G ceramic filters mainly focus on conductivity, adhesion, thermal expansion matching, or the versatility of surface pastes and hole pastes. They are still difficult to simultaneously achieve shear filling, retention locking, and sintering continuity for irregularly shaped metallized areas such as end faces, sidewalls, corners, grooves, and through-hole edges. Problems such as sidewall sagging, thinning of the silver layer at corners, insufficient filling of grooves, and local decrease in conductivity continuity still easily occur. Therefore, we propose a lead-free and environmentally friendly conductive silver paste for 5G communication filters.
[0005] To achieve the above objectives, this application adopts the following technical solution: a lead-free and environmentally friendly conductive silver paste for 5G communication filters, wherein the conductive silver paste is used in the irregular metallization region of the ceramic filter for 5G communication, and the irregular metallization region is a metallization region with height difference, hole and groove structure or adjacent surface boundary structure.
[0006] The conductive silver paste, by total mass, comprises the following components: 78.0%-82.0% silver powder, 3.0%-4.8% lead-free glass powder, 13.5%-17.5% fast recovery resident lock-type carrier, 0.4%-0.9% dispersant, 0.2%-0.7% interface modifier, and 0-0.5% additives, with the sum of the mass percentages of all components being 100%.
[0007] The silver powder is a three-level silver powder system used for film formation in irregular metallization regions. By total mass of silver powder, it includes 28%-42% flake silver powder, 42%-58% spherical silver powder and 8%-18% fine-particle silver powder.
[0008] The softening point of lead-free glass powder is 485-560℃;
[0009] Fast recovery dwell lock carriers consist of solvent, resin film-forming agent, and fast recovery thixotropic component, with the fast recovery thixotropic component accounting for 6%-12% of the total mass of the fast recovery dwell lock carrier.
[0010] Preferably, the D50 of the flake silver powder is 3.0-7.0 μm, the flake thickness is 0.10-0.25 μm, and the aspect ratio is 20-50; the D50 of the spherical silver powder is 1.2-3.2 μm; and the D50 of the fine-particle silver powder is 0.20-0.55 μm.
[0011] Preferably, the D50 of the lead-free glass powder is 0.7-1.6μm, the lead-free glass powder does not actively contain lead-containing glass components, and the lead content is less than 0.1wt%; the lead-free glass powder includes multiple components from boron oxide, silicon dioxide, zinc oxide, bismuth oxide, aluminum oxide and titanium dioxide.
[0012] Preferably, the lead-free glass powder includes a first lead-free glass powder and a second lead-free glass powder, wherein the softening point of the first lead-free glass powder is lower than that of the second lead-free glass powder.
[0013] Preferably, the mass ratio of the first lead-free glass powder to the second lead-free glass powder is 7:3, the softening point of the first lead-free glass powder is 495℃, and the softening point of the second lead-free glass powder is 555℃.
[0014] Preferably, the solvent is selected from one or more of terpineol, butyl carbitol acetate, and diethylene glycol butyl ether acetate; the resin film-forming agent is selected from one or more of ethyl cellulose, acrylic resin, and rosin-modified resin; and the fast-recovery thixotropic component includes at least two of polyamide wax, hydrogenated castor oil, hydrophobic fumed silica, and organobentonite.
[0015] Preferably, the fast-recovery thixotropic component includes polyamide wax and hydrophobic fumed silica, wherein the mass ratio of polyamide wax to hydrophobic fumed silica is 3:1-5:1;
[0016] The dispersant is selected from one or more of polyester dispersants, polyether dispersants, and hydroxyl-containing polymeric dispersants, and the acid value of the dispersant is less than 15 mg KOH / g;
[0017] The interface modifier is selected from one or more of nano alumina, nano titanium dioxide, nano zirconium oxide, and silane coupling agent, and the average particle size of the interface modifier is 20-120 nm.
[0018] Additives include at least one of leveling agents, defoamers, and anti-skinning agents.
[0019] A method for preparing a lead-free, environmentally friendly conductive silver paste for 5G communication filters includes the following steps:
[0020] S1: To prepare the basic carrier liquid, add the solvent to the reaction vessel, heat it up, add the resin film-forming agent and stir to dissolve it, cool it down and add the dispersant to obtain the basic carrier liquid;
[0021] S2: Prepare the resident lock-in mother liquor. Take a portion of the base carrier liquid and add it to the mixing tank. Add the fast recovery thixotropic component and pre-disperse it. After standing and aging, the resident lock-in mother liquor is obtained.
[0022] S3: Silver powder classification and pre-wetting: Add flake silver powder and spherical silver powder to a mixing tank, add some base carrier liquid and stir at low speed, then add fine-particle silver powder in batches and stir to obtain silver powder pre-dispersion paste.
[0023] S4: Lead-free glass powder is dispersed in the post-dispersion stage. Lead-free glass powder and interface modifier are added to the silver powder predispersed paste and stirred to obtain silver paste premix containing glass powder.
[0024] S5: Grinding and dispersing, the silver paste premix is ground in multiple passes to obtain the ground paste;
[0025] S6: Low-shear mesh formation and degassing. The ground slurry is transferred to a low-speed mixing tank, and the remaining base carrier liquid, resident lock-type mother liquor and additives are added. After low-speed stirring and vacuum degassing, conductive silver paste is obtained.
[0026] Preferably, in step S1, the heating temperature is 75-85℃, the cooling temperature is 45-55℃, and stirring is continued for 20-40 minutes after adding the dispersant;
[0027] In step S2, the pre-dispersion speed is 900-1400 r / min, the pre-dispersion time is 20-40 minutes, the standing maturation temperature is 45-55℃, and the standing maturation time is 2-8 hours;
[0028] In step S3, add a base carrier liquid that accounts for 50%-65% of the total mass of the base carrier liquid, stir at 200-400 r / min for 10-20 minutes, and then add fine silver powder in two batches, stirring at 400-650 r / min for 10-20 minutes after each addition.
[0029] In step S4, stir at 300-500 r / min for 15-30 minutes;
[0030] In step S5, the grinding is carried out sequentially using roller gaps of 45-55μm, 25-35μm, 12-18μm and 6-10μm until the scraper fineness is no greater than 10μm, and the material temperature is controlled to not exceed 45℃.
[0031] In step S6, stir at 150-300 r / min for 20-40 minutes and degas under a vacuum of -0.08 MPa to -0.095 MPa for 20-40 minutes.
[0032] The application of a lead-free and environmentally friendly conductive silver paste for 5G communication filters in irregularly shaped metallized areas of 5G communication filters includes coating the conductive silver paste onto irregularly shaped metallized areas of 5G communication ceramic filters by screen printing, scraping, pad printing or dispensing to form a wet silver layer.
[0033] The irregular metallized area includes at least one of the following: end face, side wall, corner, groove, groove wall, step edge, orifice edge, through hole edge, and the junction of adjacent surfaces;
[0034] The coated ceramic substrate was left to stand at 25-40℃ for 3-8 minutes to set, followed by gradient drying and sintering to obtain a sintered silver layer.
[0035] Gradient drying includes: first drying at 70-90℃ for 5-12 minutes, then drying at 110-130℃ for 10-20 minutes;
[0036] The sintering process includes: heating to 330-380℃ at 3-5℃ / min and holding for 10-20 minutes, then heating to 520-600℃ at 4-7℃ / min and holding for 5-15 minutes, and finally heating to 760-820℃ at 5-8℃ / min and holding for 8-18 minutes.
[0037] The technical effects and advantages of this invention are as follows:
[0038] In this invention, to address the film formation requirements of irregularly shaped metallized areas such as end faces, side walls, corners, grooves, and via edges of ceramic filters used in 5G communication, a three-level silver powder system is constructed using flake silver powder, spherical silver powder, and fine-particle silver powder. This system is combined with low-flow interface-bonded lead-free glass powder and a fast-recovery retention lock-shaped carrier. The flake silver powder facilitates the formation of in-plane overlapping conductive structures on the end faces, side walls, and corner surfaces. The spherical silver powder facilitates the construction of a sintered conductive framework. The fine-particle silver powder can compensate for local gaps at the inner corners, the bottom of the grooves, and the edges of the vias. Simultaneously, the fast-recovery retention lock-shaped carrier allows the silver paste to spread into the irregularly shaped areas under the shearing action of a doctor blade, screen, or pad printing, and to quickly recover its support state after shearing. This reduces problems such as side wall sagging, edge shrinkage, thinning of the silver layer at corners, and insufficient filling of grooves, resulting in better retention stability and film uniformity of the wet silver layer in the irregularly shaped metallized areas.
[0039] This invention also employs a series of processes including graded pre-wetting of silver powder, post-dispersion of lead-free glass powder, low-shear meshing, and gradient drying and sintering. These processes create a more harmonious interaction between the conductive framework of silver powder, the lead-free glass phase, and the ceramic matrix. Graded pre-wetting of silver powder helps maintain the wetting and overlapping state of both flake and spherical silver powders. Post-dispersion of lead-free glass powder helps reduce early separation of the silver powder contact structure by the glass powder. Low-shear meshing helps restore the thixotropic support state of the slurry. During subsequent drying and sintering, the resin film-forming agent first forms temporary support, then the lead-free glass powder participates in interfacial wetting and bonding, and the silver powder is further sintered and connected to form a continuous conductive silver layer. Thus, this invention achieves a good balance between shear filling, retention locking, sintering conductivity, and interfacial bonding, improving the thickness uniformity, conductivity continuity, and interfacial stability after thermal cycling of the sintered silver layer. It is suitable for the lead-free and environmentally friendly metallization preparation of irregularly shaped metallization areas in ceramic filters for 5G communication. Attached Figure Description
[0040] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings, the same reference numerals are used to refer to the same parts:
[0041] Figure 1 This is a flowchart illustrating the preparation method of the lead-free, environmentally friendly conductive silver paste for 5G communication filters according to the present invention.
[0042] Figure 2 A comparison of the thixotropic recovery rates of different samples at recovery times of 30s and 60s;
[0043] Figure 3 A bar chart comparing the incomplete filling rate of grooves for different samples;
[0044] Figure 4 A bar chart comparing the pull-off adhesion of different samples;
[0045] Figure 5 This is a low-magnification cross-sectional morphology image of the sintered silver layer in Example 1;
[0046] Figure 6 This is a high-magnification cross-sectional morphology diagram of the sintered silver layer in Example 1. Detailed Implementation
[0047] It is readily understood that, based on the technical solution of this invention, those skilled in the art can propose various interchangeable structural methods and implementations without altering the essential spirit of the invention. Therefore, the following detailed embodiments and accompanying drawings are merely illustrative examples of the technical solution of this invention and should not be considered as the entirety of the invention or as limitations or restrictions on the technical solution of this invention.
[0048] This invention provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters. The conductive silver paste is mainly used for irregularly shaped metallized areas such as end faces, side walls, corners, grooves, and through-hole edges of ceramic filters for 5G communication. The 5G communication filter can be a dielectric ceramic filter, a ceramic cavity filter, or a radio frequency filter component with ceramic substrate metallization requirements. Its metallized areas typically include end faces, side walls, groove walls, step edges, orifice edges, and the junctions of adjacent surfaces.
[0049] In the aforementioned irregularly shaped metallized regions, there is a continuous influence between the construction and sintering states of the conductive silver paste. The silver paste needs to possess a certain fluidity under the action of a doctor blade, screen, or printing head to spread to the sidewalls, corners, and bottom of the grooves. After the silver paste leaves the shearing action, it needs to have a rapid structural recovery capability to maintain the morphology of the wet silver layer at the sidewalls and corners. During drying and sintering, a relatively stable bonding relationship needs to be formed between the silver powder conductive framework, the lead-free glass phase, and the ceramic matrix to obtain a continuous conductive silver layer. If the high shear fluidity of the silver paste is insufficient, inadequate filling of the grooves and material shortages at the edges of through-holes may occur. If the retention and support capacity of the silver paste is insufficient, sidewall sagging, edge accumulation, or thinning of the silver layer at corners may occur. If the glass phase content or fluidity is unsuitable, it may affect the bonding stability between the silver layer and the ceramic matrix or the continuity of the silver conductive network.
[0050] Based on the above application characteristics, the conductive silver paste of the present invention, through the combination of silver powder system, lead-free glass powder, fast recovery residence lock carrier, dispersant, interface modifier and additives, enables the paste to have spreading and filling ability in the shearing stage, morphology retention ability in the residence stage, and form a conductive continuous and interfacially stable silver layer in the sintering stage.
[0051] The conductive silver paste of the present invention comprises, by weight, the following components: 78.0%-82.0% silver powder, 3.0%-4.8% lead-free glass powder, 13.5%-17.5% fast recovery resident lock-type carrier, 0.4%-0.9% dispersant, 0.2%-0.7% interface modifier, and 0-0.5% additives; provided that the content ranges of the above components are met, the sum of the contents of each component is 100%.
[0052] The silver powder is a three-stage silver powder system for forming films in irregularly shaped metallized regions. By total mass of silver powder, it includes 28%-42% flake silver powder, 42%-58% spherical silver powder, and 8%-18% fine-particle silver powder. The flake silver powder has a D50 of 3.0-7.0 μm, a flake thickness of 0.10-0.25 μm, and an aspect ratio of 20-50. The spherical silver powder has a D50 of 1.2-3.2 μm. The fine-particle silver powder has a D50 of 0.20-0.55 μm.
[0053] Flake-shaped silver powder is used to form in-plane lap conductive structures on end faces, sidewalls, and corner surfaces. Its flake shape is beneficial for forming continuous conductive surfaces under thin wet film conditions. Spherical silver powder is used to construct the sintered conductive framework. Its stacking stability is good and it is beneficial for improving the overall density of the silver layer. Fine-grained silver powder is used to enter the gap between flake-shaped and spherical silver powder and to compensate for the local discontinuous areas that are easily generated on the inner side of corners, the bottom of grooves, and the edges of through holes. The above three-level silver powder system corresponds to the film formation requirements of irregular metallization areas, so that the silver paste has spreadability in planar areas, gap filling ability in corner and groove areas, and good conductive continuity after sintering.
[0054] When the content of fine-particle silver powder is less than 8%, the gap-filling compensation ability at the bottom of the groove and the inner side of the corner is weak, and local weak conductive areas are prone to appear after sintering. When the content of fine-particle silver powder is higher than 18%, the total specific surface area of silver powder increases, the adsorption of the system on the carrier increases, the high shear viscosity of the slurry may increase, the filling stability at the bottom of the groove decreases, and the porosity may also increase after sintering. Therefore, the content of fine-particle silver powder is controlled at 8%-18%, preferably 12%-16%.
[0055] The lead-free glass powder is a low-flow interfacial bonding type lead-free glass powder with a softening point of 485-560℃ and a D50 of 0.7-1.6μm. No lead-containing glass components are actively added, and the lead content is preferably less than 0.1wt%. The lead-free glass powder includes multiple components from boron oxide, silicon dioxide, zinc oxide, bismuth oxide, aluminum oxide, and titanium dioxide. Among them, boron oxide and bismuth oxide are used to adjust the softening temperature of the glass powder and improve its wettability to the ceramic matrix, silicon dioxide and aluminum oxide are used to limit excessive flow of the glass phase, and zinc oxide and titanium dioxide are used to improve the interfacial bonding between the silver layer and the ceramic matrix.
[0056] During sintering, the lead-free glass powder can form an interfacial bonded microphase between the silver layer and the ceramic matrix. When the lead-free glass powder content is less than 3.0%, there are fewer bonding points between the silver layer and the ceramic matrix after sintering, and local edge lifting is likely to occur after thermal cycling or subsequent bonding. When the lead-free glass powder content is higher than 4.8%, the proportion of the glass phase inside the silver conductive network is too high, and the sheet resistance of the sintered silver layer may increase. Therefore, the lead-free glass powder content is controlled at 3.0%-4.8%, preferably 3.4%-4.3%.
[0057] The fast-recovery retention lock-type carrier comprises a solvent, a resin film-forming agent, and a fast-recovery thixotropic component; the solvent may be selected from one or more of terpineol, butyl carbitol acetate, and diethylene glycol butyl ether acetate; the resin film-forming agent may be selected from one or more of ethyl cellulose, acrylic resin, and rosin-modified resin; the fast-recovery thixotropic component comprises at least two of polyamide wax, hydrogenated castor oil, hydrophobic fumed silica, and organobentonite; preferably, the fast-recovery thixotropic component comprises polyamide wax and hydrophobic fumed silica in a mass ratio of 3:1 to 5:1.
[0058] The fast-recovery thixotropic component accounts for 6%-12% of the total mass of the fast-recovery resident lock-shaped carrier. In this invention, the fast-recovery thixotropic component is used to form a recoverable thixotropic network inside the carrier. Under the shearing action of a doctor blade or screen, the thixotropic network is temporarily disrupted, and the viscosity of the paste decreases, which is conducive to entering the sidewall, corner, and groove areas. When the silver paste is released from shearing and stays on the ceramic irregular metallization area, the thixotropic network gradually recovers, giving the wet silver layer a certain support force, thereby reducing sidewall sagging and edge shrinkage. When the fast-recovery thixotropic component is less than 6%, the thixotropic recovery is insufficient, and the tendency of the silver paste to slide down the sidewall area increases. When it is more than 12%, the high-shear viscosity of the silver paste is too high, and the filling at the bottom of the groove and the edge of the through hole may be affected.
[0059] During the residence and gradient drying stages, the fast recovery thixotropic component mainly provides initial morphological support for the wet silver layer. The resin film-forming agent forms temporary film-forming support as the solvent evaporates, keeping the silver powder stacking structure relatively stable before the binder is removed. During the subsequent heating process, the organic components are gradually removed, the lead-free glass powder begins to soften and participates in interface wetting, and the silver powder particles are further sintered and connected, so that the morphology of the irregular metallized region silver layer formed in the early stage continues to the sintered silver layer.
[0060] The dispersant is used to improve the dispersion state of silver powder, lead-free glass powder, and interface modifier in the carrier, and can be selected from one or more of polyester dispersants, polyether dispersants, and hydroxyl-containing polymeric dispersants. The acid value of the dispersant is preferably less than 15 mg KOH / g, so as to reduce the excessive adsorption or unstable interaction between the acidic groups in the dispersant and the surface of lead-free glass powder during storage, mixing, or low-temperature drying, reduce the risk of glass powder agglomeration and slurry rheological fluctuations, and help lead-free glass powder maintain relatively stable wetting and interfacial bonding behavior during the sintering stage.
[0061] The interface modifier can be selected from one or more of nano-alumina, nano-titanium dioxide, nano-zirconia, and silane coupling agents. The average particle size of the interface modifier is preferably 20-120 nm. It is used to assist the lead-free glass phase in forming dispersed binding points at the interface between the silver layer and the ceramic matrix, and to reduce the tendency of the glass phase to continuously accumulate inside the silver layer. When the content of the interface modifier is less than 0.2%, the interface modulation effect is weak; when it is more than 0.7%, the content of insulating oxide is too high, which may affect the continuity of the silver conductive network.
[0062] The additives include at least one of leveling agents, defoamers, and anti-skinning agents, with a total content not exceeding 0.5%. The additives are used to improve defoaming, printing edges, and storage conditions, and can be selected according to the specific printing method and equipment conditions.
[0063] This invention also provides a method for preparing lead-free, environmentally friendly conductive silver paste for 5G communication filters. The method includes steps such as preparation of a base carrier solution, preparation of a resident lock-type mother liquor, graded pre-wetting of silver powder, post-dispersion of lead-free glass powder, grinding and dispersion, low-shear web formation, and degassing. This preparation process can be found in [reference needed]. Figure 1 The flowchart shown is as follows: Figure 1 The main process of preparing the conductive silver paste of this invention is summarized in flowchart form, which helps to intuitively understand the sequential relationship and interrelationship between each process; the steps are as follows:
[0064] S1: To prepare the basic carrier solution, add the solvent to the reaction vessel, heat to 75-85℃, add the resin film-forming agent, and stir until completely dissolved to obtain a resin solution; cool the resin solution to 45-55℃, add the dispersant, and continue stirring for 20-40 minutes to obtain the basic carrier solution.
[0065] S2: Prepare the resident lock mother liquor. Take a portion of the base carrier liquid and add it to a mixing tank. Add polyamide wax and hydrophobic fumed silica. Pre-disperse at 900-1400 r / min for 20-40 minutes. Then let it stand and mature at 45-55℃ for 2-8 hours to obtain the resident lock mother liquor. The preferred maturation time is 4-6 hours.
[0066] In this step, the pre-dispersion and maturation process is beneficial for the thixotropic component to form a relatively stable recoverable network in the resin carrier. When the maturation time is less than 2 hours, the swelling and network formation of the thixotropic component in the carrier may be insufficient, and the viscosity of the slurry will fluctuate greatly. When the maturation time exceeds 8 hours, the improvement of the thixotropic recovery rate is not obvious, and further extending the maturation time is not conducive to the production cycle.
[0067] S3: Silver powder classification and pre-wetting. Add flake silver powder and spherical silver powder to a mixing tank, add a base carrier liquid accounting for 50%-65% of the total mass of the base carrier liquid, and stir at a low speed of 200-400 r / min for 10-20 minutes to allow the flake silver powder and spherical silver powder to first form a basic conductive framework; then add fine-particle silver powder in two batches, stirring at 400-650 r / min for 10-20 minutes after each addition, so that the fine-particle silver powder gradually enters the gap between the flake silver powder and the spherical silver powder to obtain silver powder pre-dispersion paste.
[0068] In this step, the flake silver powder and spherical silver powder are pre-wetted, and then fine-particle silver powder is added in batches. This helps to reduce the preferential adsorption of fine-particle silver powder on the carrier, so that the flake silver powder is kept in a better wetted state. At the same time, it can reduce the curling or breakage of the flake silver powder under long-term high shear conditions, and preserve its in-plane conductive overlap.
[0069] S4: Disperse the lead-free glass powder in the post-dispersion stage. Add the lead-free glass powder and interface modifier to the silver powder predispersed paste and stir at 300-500 r / min for 15-30 minutes to obtain the silver paste premix containing glass powder.
[0070] In this step, the lead-free glass powder is added after the silver powder is pre-dispersed. This helps to complete the wetting of the flake and spherical silver powder and the formation of the basic conductive framework first, reduces the competitive adsorption of the glass powder and fine-particle silver powder on the carrier, and also reduces the possibility of the glass powder entering the silver powder contact gap and causing local separation in the early mixing stage. In the subsequent grinding process, the lead-free glass powder can still be dispersed in the slurry and participate in the wetting of the ceramic interface and local sealing during the sintering stage.
[0071] S5: Grinding and dispersing. The silver paste premix is fed into a three-roll mill and subjected to multiple grinding passes with roller gaps of 45-55μm, 25-35μm, 12-18μm and 6-10μm, until the scraper fineness is no greater than 10μm. During the grinding process, the material temperature is controlled to not exceed 45℃ to reduce the evaporation of carrier solvent and the instability of thixotropic components.
[0072] S6: Low-shear mesh formation and degassing. The ground slurry is transferred to a low-speed mixing tank, and the remaining base carrier liquid, retention lock-in masterbatch, leveling agent and defoamer are added. The mixture is stirred at 150-300 r / min for 20-40 minutes to make the slurry form a rheological state suitable for printing irregularly shaped metallized areas. Then, it is degassed at a vacuum degree of -0.08MPa to -0.095MPa for 20-40 minutes to obtain lead-free environmentally friendly conductive silver paste for 5G communication filters.
[0073] The present invention also provides the application of the above-mentioned conductive silver paste in the irregular metallization area of a 5G communication filter. The application includes: applying the conductive silver paste to the end face, side wall, corner, groove or through-hole edge area of a 5G communication ceramic filter by screen printing, scraping, pad printing or dispensing to form a wet silver layer; leaving the coated ceramic substrate at 25-40°C for 3-8 minutes to allow the silver paste to complete thixotropic recovery in the irregular metallization area; and then performing gradient drying and sintering treatment to obtain a sintered silver layer.
[0074] Gradient drying includes: first drying at 70-90℃ for 5-12 minutes to allow some solvent to evaporate slowly and reduce rapid shrinkage of the wet film; then drying at 110-130℃ for 10-20 minutes to allow the resin film-forming agent to form temporary support; sintering treatment includes: heating at 3-5℃ / min to 330-380℃ and holding for 10-20 minutes to remove organic components; then heating at 4-7℃ / min to 520-600℃ and holding for 5-15 minutes to allow the lead-free glass powder to soften and form an interfacial bonding microphase; finally heating at 5-8℃ / min to 760-820℃ and holding for 8-18 minutes to sinter and densify the silver powder, forming a continuous conductive silver layer.
[0075] When the dwell time is less than 3 minutes, the fast recovery thixotropic network has not been fully rebuilt, and the sidewall area may still slip. When the dwell time exceeds 8 minutes, it has a significant impact on the continuous production cycle, and some solvents evaporate under uncontrolled conditions, which may cause slight shrinkage at the edge of the wet film. Therefore, the dwell time is preferably 4-6 minutes.
[0076] The technical solutions of the present invention are further illustrated below through embodiments and comparative examples. The described embodiments are only for illustrating the present invention and do not constitute a limitation on the scope of protection of the present invention. After reading the contents of the present invention, those skilled in the art may make non-substantial modifications or adjustments to the technical solutions of the present invention, which shall still fall within the scope of protection of the present invention. Unless otherwise specified, the raw materials used in each embodiment and comparative example are all commercially available products.
[0077] Example 1: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters. By total mass, the conductive silver paste comprises 79.0% silver powder, 3.8% lead-free glass powder, 15.6% fast recovery dwell lock-type carrier, 0.6% polyester dispersant, 0.5% nano titanium dioxide interface modifier, 0.2% defoamer, and 0.3% leveling agent.
[0078] The silver powder has a mass ratio of flake silver powder, spherical silver powder and fine-particle silver powder of 34:51:15; the flake silver powder has a D50 of 5.0 μm and a flake thickness of 0.16 μm; the spherical silver powder has a D50 of 2.1 μm; and the fine-particle silver powder has a D50 of 0.35 μm.
[0079] The lead-free glass powder has a softening point of 520℃ and a D50 of 1.1μm. Based on the total mass of the lead-free glass powder, it includes 25% boron oxide, 23% silicon dioxide, 24% zinc oxide, 17% bismuth oxide, 7% aluminum oxide, and 4% titanium dioxide.
[0080] In the fast-recovery residency lock-type carrier, the mass ratio of solvent, resin film-forming agent, and fast-recovery thixotropic component is 74:17:9; the solvent is a mixed solvent composed of terpineol and butyl carbitol acetate in a mass ratio of 6:4; the resin film-forming agent is composed of ethyl cellulose and acrylic resin in a mass ratio of 7:3; and the fast-recovery thixotropic component is composed of polyamide wax and hydrophobic fumed silica in a mass ratio of 4:1.
[0081] The preparation method of this embodiment includes the following steps:
[0082] S1: Add the mixed solvent to the reaction vessel, heat to 80°C, add ethyl cellulose and acrylic resin, stir until completely dissolved, cool to 50°C, add polyester dispersant, and continue stirring for 30 minutes to obtain the basic carrier liquid;
[0083] S2: Take a portion of the base carrier liquid and add it to the mixing tank. Add polyamide wax and hydrophobic fumed silica. Pre-disperse at 1200 r / min for 30 minutes, and then let it stand and mature at 50℃ for 4 hours to obtain the resident lock-type mother liquor.
[0084] S3: Add flake silver powder and spherical silver powder to a mixing tank, add a base carrier liquid that accounts for 60% of the total mass of the base carrier liquid, and stir at 300 r / min for 15 minutes; then add fine-particle silver powder in two batches, stirring at 500 r / min for 15 minutes after each addition to obtain silver powder pre-dispersion paste.
[0085] S4: Add lead-free glass powder and nano titanium dioxide to the silver powder predispersed paste, and stir at 400 r / min for 20 minutes to obtain silver paste premix;
[0086] S5: Feed the silver paste premix into a three-roll mill and grind it in four passes with roller gaps of 50μm, 30μm, 15μm and 8μm in sequence. The fineness of the scraper after grinding is 8μm.
[0087] S6: Transfer the ground slurry to a low-speed mixing tank, add the remaining base carrier liquid, retention lock mother liquor, defoamer and leveling agent, stir at 250 r / min for 30 minutes, and then degas under a vacuum of -0.09 MPa for 30 minutes to obtain conductive silver paste.
[0088] In this embodiment, the conductive silver paste is applied to the end face, sidewall, corner, and groove areas of the ceramic simulation part by screen printing. The wet film thickness is controlled at 22±3μm. After printing, it is left to stand at 30℃ for 5 minutes to set. Then, it is dried at 80℃ for 10 minutes and at 120℃ for 15 minutes. Then, it is heated to 350℃ at 5℃ / min and held for 15 minutes, heated to 560℃ at 6℃ / min and held for 10 minutes, and heated to 800℃ at 6℃ / min and held for 12 minutes. After cooling, a sintered silver layer is obtained.
[0089] Example 2: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters and its preparation method. The difference from Example 1 is that the mass ratio of flake silver powder, spherical silver powder, and fine-particle silver powder in the silver powder is adjusted to 31:51:18. After increasing the proportion of fine-particle silver powder, the filling capacity of the bottom of the groove, the edge of the through hole, and the inner side of the corner is enhanced. The remaining components, preparation method, and application process of this example are the same as those of Example 1.
[0090] Example 3: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters and its preparation method. The difference from Example 1 is that the mass ratio of solvent, resin film-forming agent, and fast recovery thixotropic component in the fast recovery dwelling lock carrier is adjusted to 72:17:11, and the mass ratio of polyamide wax and hydrophobic fumed silica is 5:1. After increasing the proportion of fast recovery thixotropic component, the dwelling and shaping ability of the sidewall region and the region with a large height difference is enhanced. The S6 low shear mesh formation time in this example is 40 minutes, and the remaining components and processes are the same as in Example 1.
[0091] Example 4: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters and its preparation method. The difference from Example 1 is that the silver powder content is adjusted to 78.3%, the lead-free glass powder content is adjusted to 4.5%, and the contents of the remaining components are the same as in Example 1. The lead-free glass powder is composed of low softening point glass powder and high softening point glass powder in a mass ratio of 7:3. The softening point of the low softening point glass powder is 495℃, and the softening point of the high softening point glass powder is 555℃. The low softening point glass powder is used to preferentially wet the ceramic matrix during the intermediate temperature stage of sintering, and the high softening point glass powder is used to improve the flow boundary of the glass phase. The remaining processes in this example are the same as in Example 1.
[0092] Example 5: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters and its preparation method. Based on the total mass of the conductive silver paste, it includes 79.9% silver powder, 3.0% lead-free glass powder, 15.5% fast recovery resident lock-type carrier, 0.6% polyester dispersant, 0.5% nano-titanium dioxide interface modifier, 0.2% defoamer, and 0.3% leveling agent. The mass ratio of flake silver powder, spherical silver powder, and fine-particle silver powder in the silver powder is 38:53:9. The fast recovery thixotropic component accounts for 6.5% of the total mass of the fast recovery resident lock-type carrier, wherein the mass ratio of polyamide wax and hydrophobic fumed silica is 3:1. This example illustrates the implementation effect when the fine-particle silver powder, lead-free glass powder, and fast recovery thixotropic component are close to the lower limit of this invention. The remaining processes in this example are the same as in Example 1.
[0093] Example 6: This example provides a lead-free, environmentally friendly conductive silver paste for 5G communication filters and its preparation method. The difference from Example 1 is that the conductive silver paste is coated onto the surface of a ceramic simulation part with steps and through-hole edges by pad printing. The dwell time after printing is 6 minutes, the maximum sintering temperature is 780℃, and the holding time is 15 minutes. This example is used to illustrate that the silver paste of the present invention can be applied to pad printing or partial transfer printing to form irregularly shaped metallized silver layers. Since the conductive silver paste formulation of this example is the same as that of Example 1, the subsequent experimental examples mainly use Example 1 as the performance evaluation sample of this formulation.
[0094] To further illustrate the impact of key technical features on the performance of conductive silver paste, the following comparative examples were set up; each comparative example was based on Example 1, with one key variable adjusted to examine its impact on the film formation, conductivity, and adhesion reliability of the irregularly shaped metallized region.
[0095] Comparative Example 1: This comparative example is basically the same as Example 1, except that the three-stage silver powder system is replaced with an equal amount of single spherical silver powder with a D50 of 2.0 μm. No flake silver powder or fine-particle silver powder is added. This comparative example examines the effect of the single spherical silver powder system on the corner and groove filling of irregular metallization regions.
[0096] Comparative Example 2: This comparative example is basically the same as Example 1, except that the proportion of fine-particle silver powder in the silver powder is reduced to 5%, and the mass ratio of flake silver powder, spherical silver powder and fine-particle silver powder is 36:59:5; This comparative example examines the effect of low fine-particle silver powder on the continuity of the silver layer at the bottom of the groove and the corner.
[0097] Comparative Example 3: This comparative example is basically the same as Example 1, except that the proportion of fine-particle silver powder in the silver powder is increased to 24%, and the mass ratio of flake silver powder, spherical silver powder and fine-particle silver powder is 28:48:24; This comparative example examines the effect of a higher proportion of fine-particle silver powder on the viscosity of the slurry, the film-forming state and the continuity of sintering conductivity.
[0098] Comparative Example 4: This comparative example is basically the same as Example 1, except that no fast recovery thixotropic component is added, the fast recovery retention lock-type carrier is replaced with a common ethyl cellulose resin carrier, and the low shear viscosity is made close to that of Example 1 by adjusting the resin content; this comparative example examines the effect of the carrier's thixotropic recovery ability on the retention and shaping of the sidewall.
[0099] Comparative Example 5: This comparative example is basically the same as Example 1, except that the fast recovery thixotropic component accounts for 16% of the total mass of the fast recovery residence lock-shaped carrier; this comparative example examines the effect of a higher thixotropic component on shear spreading and groove filling.
[0100] Comparative Example 6: The formulation of this comparative example is the same as that of Example 1, except that it is prepared by a one-time mixing process. That is, silver powder, lead-free glass powder, dispersant, carrier, interface modifier and additives are added to the mixing tank, and after high-speed stirring, they are subjected to three-roll milling. The steps of silver powder classification and pre-wetting, lead-free glass powder post-dispersion and low-shear network formation are not used. This comparative example examines the effect of the preparation sequence on the fineness, rheological state and sintering performance of the slurry.
[0101] Comparative Example 7: This comparative example is basically the same as Example 1, except that after printing, no residence setting and gradient drying are performed. Instead, after printing, the sample is dried directly at 120°C for 30 minutes and then sintered according to the sintering regime of Example 1. This comparative example examines the effect of the application process on the wet film stability of the irregular metallized area.
[0102] Comparative Example 8: This comparative example is basically the same as Example 1, except that the silver powder content is adjusted to 81.3%, the lead-free glass powder content is reduced to 1.5%, and the contents of the remaining components are the same as in Example 1; this comparative example examines the effect of low lead-free glass powder content on interfacial bonding ability.
[0103] Comparative Example 9: This comparative example is basically the same as Example 1, except that the silver powder content is adjusted to 76.6%, the lead-free glass powder content is increased to 6.2%, and the contents of the remaining components are the same as in Example 1; this comparative example examines the effect of higher lead-free glass powder content on the silver conductive network and sheet resistance.
[0104] To verify the technical effectiveness of the present invention, performance tests were conducted on the conductive silver paste and sintered silver layer prepared in the above embodiments and comparative examples. The experimental examples were designed around the technical problems of the present invention, mainly evaluating the paste fineness, shear activation and retention lock-in ability, film stability of irregularly shaped metallized regions, conductivity after sintering, adhesion reliability, and representative cross-sectional morphology. To make the test results more intuitive, based on the tabular test data, the present invention further selected representative embodiments and comparative examples to draw... Figures 2 to 4 and combined Figure 5 and Figure 6 Microscopic morphology analysis was performed.
[0105] Experimental Example 1: This experimental example is used to evaluate whether conductive silver paste has the basic properties suitable for construction in irregularly shaped metallized areas and the ability to quickly recover and retain the shape.
[0106] The fineness test of the scraper was conducted according to the method specified in GB / T 1724. A scraper fineness tester was used to measure the fineness of the slurry after grinding. Viscosity and thixotropic recovery properties were tested using a rotational rheometer at 25℃. The test was conducted first at 1 second... -1 The initial viscosity η0 was tested at the shear rate, and then at 100 s. -1 Shearing was performed at the shear rate for 60 seconds, and the high shear viscosity ηh was recorded, followed by recovery to 1 second. -1 Shear rate was set and allowed to stand for 30 seconds and 60 seconds respectively, and the recovered viscosity η30 and η60 were tested; the thixotropic recovery rates R30 and R60 were calculated according to the following formulas: R30 = η30 / η0 × 100%; R60 = η60 / η0 × 100%;
[0107] Simultaneously, each sample was printed onto the surface of an alumina ceramic simulation part with 90° sidewalls, with the wet film thickness controlled at 22±3μm. After printing, the sample was placed vertically at 25℃ for 10 minutes, and the maximum length of the slurry flowing downwards in the sidewall area was measured and recorded as the sag length. Three samples were tested for each sample, and the average value was taken. The test results are shown in Table 1. Table 1. Basic properties and thixotropic recovery properties of the slurry Example 1 8 58.4 15.6 71.2 83.7 0.42 Example 2 8.5 62.7 17.4 67.5 80.1 0.51 Example 3 8 66.5 18.2 76.8 87.8 0.3 Example 4 8 59.6 16.1 70.6 83.6 0.45 Example 5 9 54.2 15 63.4 78 0.66 Comparative Example 1 8 55.6 16.8 55.8 69.6 0.92 Comparative Example 2 8.5 53.8 15.9 60.2 74.5 0.76 Comparative Example 3 10 74.5 26.8 62.1 77.7 0.62 Comparative Example 4 8 57.1 31.4 32.5 51.8 2.35 Comparative Example 5 9.5 81.6 36.5 72.6 85 0.21 Comparative Example 6 11 60.2 20.3 45.4 62.3 1.26 Comparative Example 7 8 58.2 15.7 71 83.5 0.43 Comparative Example 8 8 56.9 15.5 70.1 83 0.44 Comparative Example 9 8.5 61.7 17.2 71.3 83.6 0.39
[0108] To facilitate a direct comparison of the differences between different systems during the short-term recovery process, the thixotropic recovery rates of Examples 1, 3, 4, and 5 at recovery times of 30 s and 60 s were plotted. Figure 2, Figure 2 Corresponding to the data in Table 1, the lines in the figure are only used to indicate the trend of change of each sample between two test time points, and do not represent that the thixotropic recovery rate changes strictly linearly between 30s and 60s.
[0109] From Table 1 and in combination Figure 2 It can be seen that the squeegee fineness of Examples 1-5 is no greater than 10μm, which can meet the fineness requirements of screen printing and coating of irregularly shaped metallized areas; Examples 1-4 achieve a fineness of 100s. -1 Under high shear conditions, the viscosity decreased significantly. The thixotropic recovery rate was 67.5%-76.8% after 30 seconds of shear cessation and 80.1%-87.8% after 60 seconds of shear cessation. The sag length did not exceed 0.51 mm, indicating that it has good shear spreading ability and short-term residence recovery ability. Example 5 is close to the lower limit of fine-particle silver powder, lead-free glass powder and thixotropic components. The thixotropic recovery rate and sag control are slightly lower than those of Example 1, but it can still maintain basic construction stability.
[0110] from Figure 2 It can be further seen that the thixotropic recovery rate of Example 3 is higher than that of Example 1 at both time points, indicating that appropriately increasing the proportion of fast recovery thixotropic component is beneficial to enhancing the short-term structural recovery ability; the recovery rate of Comparative Example 4 is significantly lower, indicating that when there is a lack of fast recovery thixotropic structure, the slurry is difficult to establish effective support after shearing; although Comparative Example 5 has a higher recovery rate, its high shear viscosity is significantly increased, indicating that while its static recovery ability is enhanced, the shear spreading resistance is also increased. This characteristic will be further reflected in the subsequent Experiment 2 as a decrease in groove filling ability.
[0111] Experiment Example 2: This experiment example is used to evaluate the film formation stability of conductive silver paste in the irregular metallization area of 5G communication filter. Since the comprehensive film formation evaluation of end face, side wall, corner, groove and through hole edge involves a variety of local morphologies, this experiment example uses a simulated filter ceramic component for comparative testing under the same conditions. The simulated component is made of alumina ceramic and has a planar end face, vertical side wall, 90° corner, 0.6mm wide groove and 1.0mm diameter through hole edge.
[0112] The conductive silver pastes obtained from each embodiment and comparative example were coated onto the surface of the simulated parts under the same screen printing conditions, and the wet film thickness was controlled to be 22±3μm. Examples 1-5, comparative examples 1-6 and comparative examples 8-9 all adopted the residence shaping and gradient drying process. Comparative example 7 adopted the direct drying process, and the sintering conditions were all 800℃ for 12 minutes.
[0113] The thickness of the sintered silver layer was tested using metallographic microscopy and cross-sectional image analysis. The average thickness in the planar area was denoted as Tp, and the minimum thickness at the corner was denoted as Tc. The corner thickness retention rate was calculated as Tc / Tp × 100%. The groove filling integrity rate was calculated as the percentage of the continuous silver layer coverage length at the bottom of the groove to the total length of the groove. The thickness variation coefficient was calculated as the ratio of the standard deviation of the thickness at multiple test points to the average thickness. Five samples were tested in each group, and no fewer than eight test points were taken for each sample. The test results are shown in Table 2. Table 2. Test results of film stability in irregularly shaped metallized regions Example 1 12.8 11.2 84.6 94.1 Example 2 13.1 10.5 86.8 96 Example 3 12.5 12 83.9 92.7 Example 4 12.7 11.6 83.5 93.5 Example 5 12.3 13.4 80.2 90.8 Comparative Example 1 11.6 21.8 63.4 73.9 Comparative Example 2 11.9 18.7 69.5 80.6 Comparative Example 3 12.1 17.9 72.4 82.2 Comparative Example 4 11.2 27.5 57.8 68.7 Comparative Example 5 10.8 20.4 65.6 70.5 Comparative Example 6 11.7 19.6 70.1 78.9 Comparative Example 7 11.4 23.2 62.8 74.4 Comparative Example 8 12.6 12.3 82.7 91.5 Comparative Example 9 12.9 13.1 81.8 90.9
[0114] To more intuitively demonstrate the differences in film formation in the groove region among different samples, the groove filling completeness rates of Examples 1, 2, 3, Comparative Example 1, and Comparative Example 5 were plotted. Figure 3 , Figure 3 Based on the relevant test results in Table 2, the differences in groove filling among the samples are highlighted using a bar chart.
[0115] From Table 2 and in combination Figure 3 As can be seen, Examples 1-5 can form relatively stable sintered silver layers on irregularly shaped ceramic simulation parts, with a thickness variation coefficient of 10.5%-13.4%, a corner thickness retention rate of 80.2%-86.8%, and a groove filling integrity rate of 90.8%-96.0%. These results indicate that the three-level silver powder system and the fast-recovery residence lock carrier are beneficial to improving the spreading, filling, and residence shaping effects on irregularly shaped metallized areas.
[0116] In Example 2, due to the increased proportion of fine-particle silver powder, the groove filling integrity rate and corner thickness retention rate were slightly better than in Example 1, indicating that fine-particle silver powder has a positive effect on corner and groove filling. In Example 3, compared to Example 1, the proportion of fast-recovery thixotropic component was increased, resulting in better sagging control, but the corner thickness retention rate and groove filling integrity rate did not improve further, indicating that the enhanced thixotropic structure has a certain impact on filling narrow areas. In Comparative Example 5, the proportion of fast-recovery thixotropic component was further increased to 16%. Although the sagging length was smaller, the high-shear viscosity increased significantly, and the corner thickness retention rate and groove filling integrity rate decreased to 65.6% and 70.5%, respectively. Figure 3 It can also be clearly seen that its groove filling ability is significantly lower than that of Examples 1-3, indicating that when the thixotropic component is too high, the ability of the slurry to spread under shear and enter the groove and corner areas is limited.
[0117] The corner thickness retention rate and groove filling integrity rate of Comparative Example 1 were significantly reduced, indicating that the adaptability of single spherical silver powder to corner and groove areas is weak. In Comparative Example 2, the content of fine-particle silver powder was low, and the bottom of the groove and the inner side of the corner were not filled. In Comparative Example 3, the content of fine-particle silver powder was high, and the film uniformity did not continue to improve, which may be related to the increase in system viscosity and local agglomeration of fine powder. Comparative Example 4 lacked a fast recovery thixotropic structure, and the sagging and thickness unevenness were relatively obvious. The results of Comparative Examples 6 and 7 show that the preparation sequence and the post-printing residence and shaping process affect the film stability of irregular metallized areas.
[0118] Experimental Example 3: This experimental example is used to evaluate whether the sintered silver layer maintains electrical continuity and interface reliability while achieving residence and shaping.
[0119] The conductive silver pastes obtained in each embodiment and comparative example were printed onto the surface of alumina ceramic substrates and irregularly shaped ceramic simulation parts, and sintered using the same process as in Experimental Example 2. After sintering, sheet resistance was tested according to the relevant methods for testing the performance of conductor pastes in the GB / T 17473 series standards. Five locations were tested for each sample, and the average value was taken. Cross-cut adhesion screening was performed according to the method specified in GB / T 9286, using a cross-cut knife with a spacing of 1 mm. The silver layer peeling after the tape was removed was observed, and the grade was recorded. Quantitative adhesion was tested using a pull-off fixture. Five samples were tested for each group, and the average value was taken. The thermal cycling test conditions were -40℃ to 125℃, with each temperature held for 30 minutes, and the transition time not exceeding 5 minutes. A total of 100 cycles were performed. After the cycles, the sheet resistance change rate and adhesion retention rate were tested. The test results are shown in Table 3. Table 3 Electrical conductivity, adhesion properties, and thermal cycling stability of the sintered silver layer Example 1 4.6 Level 0 12.8 6.4 89.6 Example 2 4.9 Level 0 12.2 7.1 88.4 Example 3 5.1 Level 0 12.5 7.5 87.8 Example 4 5 Level 0 14.1 6.8 91.2 Example 5 5.4 Level 1 10.9 8.6 84.7 Comparative Example 1 7.8 Level 2 8.5 15.6 73.4 Comparative Example 2 6.9 Level 1 9.4 13.2 78.6 Comparative Example 3 8.4 Level 2 8.9 16.8 75.1 Comparative Example 4 8.9 Level 2 7.8 19.4 69.8 Comparative Example 5 8.2 Level 2 8.2 17.1 72.5 Comparative Example 6 7.2 Level 1 9.6 14.5 79.2 Comparative Example 7 7.6 Level 2 8.8 16.3 74 Comparative Example 8 5.7 Level 2 6.5 18.8 62.7 Comparative Example 9 8.7 Level 0 15.3 10.4 88.9
[0120] To more intuitively reflect the effect of changes in lead-free glass powder content on interfacial bonding performance, the pull-off adhesion of Examples 1, 4, Comparative Example 8, and Comparative Example 9 was plotted. Figure 4 , Figure 4 The bar chart comparison results shown correspond to the pull-off adhesion data in Table 3, and can clearly reflect the differences in adhesion performance when the glass phase is insufficient, moderate, or excessive.
[0121] From Table 3 and in combination Figure 4 As can be seen, the sheet resistance of Examples 1-5 is 4.6-5.4 mΩ·□ -1 The cross-cut adhesion rating of Examples 1-4 is 0, the pull-off adhesion is 12.2-14.1 MPa, and the sheet resistance change rate after thermal cycling is less than 8%. The above results show that under the formulation and process conditions of the present invention, the retention and shaping performance and the sintering conductivity can be well balanced, and the silver layer and the ceramic substrate have good bonding stability.
[0122] Example 4, due to the use of dual-softening-point glass powder, exhibits improved pull-off adhesion compared to Example 1. Figure 4 The lead-free glass powder in the control sample also showed a relatively high column value, but the sheet resistance was slightly higher, which may be related to the glass phase participating in interfacial bonding and having a slight impact on the silver conductive network; the lead-free glass powder content in the control sample 8 was relatively low. Figure 4 The pull-off adhesion of the sample was significantly lower than that of Examples 1 and 4, and the adhesion retention rate decreased significantly after thermal cycling, indicating that the interface reliability was weak when the glass phase was insufficient. In Comparative Example 9, the lead-free glass powder content was relatively high, and the pull-off adhesion was further increased. However, as shown in Table 3, its sheet resistance also increased significantly, which may be related to the sintering contact of the silver powder in the separating part after the glass phase ratio was increased. At the same time, the difference in thermal expansion between the glass phase, the silver layer, and the ceramic matrix may also introduce local micro-defects during the cooling process, thereby affecting the continuity of electrical conductivity. Therefore, Figure 4 Together with Table 3, it can be seen that lead-free glass powder not only affects the interfacial bonding strength, but also the integrity of the conductive network of the silver layer. The range of glass powder defined in this invention is beneficial to achieving a balance between conductivity and adhesion reliability.
[0123] The results of Comparative Examples 1-7 show that silver powder gradation, thixotropic structure, segmented preparation, and dwell drying process all affect the final conductivity and adhesion reliability.
[0124] Experiment Example 4: Observation of the cross-sectional morphology of the sintered silver layer;
[0125] This experimental example is used to observe the cross-sectional structure of the sintered silver layer obtained in Example 1, so as to further illustrate the microstructure of the silver layer formed after the conductive silver paste of the present invention is coated with irregular metallization region, retained and shaped, gradient dried and sintered.
[0126] The sintered sample obtained in Example 1 was subjected to cross-sectional cutting, embedding, grinding and polishing, and then the cross-sectional morphology of the silver layer was observed using a scanning electron microscope. Figure 5 This is a low-magnification cross-sectional morphology image of the sintered silver layer in Example 1. Figure 6 This is a high-magnification cross-sectional morphology image of the sintered silver layer in Example 1.
[0127] from Figure 5 As can be seen, the sintered silver layer obtained in Example 1 is located on the surface of the ceramic substrate. The silver layer is in a continuous covering state, and the interface between the silver layer and the ceramic substrate is relatively continuous. No obvious large-area delamination or through cracks were observed. The low magnification cross-sectional morphology shows that, under the formulation and process conditions of Example 1, the conductive silver paste can form a sintered silver layer with relatively uniform thickness and relatively stable interface bonding on the surface of the ceramic substrate.
[0128] from Figure 6As can be seen, the sintered silver layer contains a continuous structure formed by the sintering and connection of silver particles. The pores are mainly dispersed and no obvious through channels are observed. The interface region of the silver layer near the ceramic substrate is relatively close, and small bonding areas are visible in some areas. This high-magnification cross-sectional morphology indicates that the flake silver powder, spherical silver powder and fine-particle silver powder in Example 1 can form a relatively continuous conductive connection structure after sintering. Lead-free glass powder can participate in wetting and bonding at the interface between the silver layer and the ceramic substrate. The fast recovery residence lock carrier plays an auxiliary role in maintaining the morphology of the wet silver layer during the early residence and drying stages.
[0129] Based on the test results of Experiment 2 and Experiment 3, it can be seen that Example 1 exhibits good thickness uniformity, corner thickness retention rate and groove filling integrity rate in the irregular metallized area, while also having low sheet resistance and high pull-off adhesion. Figure 5 and Figure 6 The cross-sectional morphology shown corroborates the test results of Example 1, indicating that under the formulation and process conditions of Example 1, the three-level silver powder system, low-flow interface-bonded lead-free glass powder, and fast-recovery residence lock-type carrier of the present invention can work together to form a sintered silver layer with continuous structure, dispersed pores, and relatively stable interface.
[0130] In summary, the lead-free, environmentally friendly conductive silver paste for 5G communication filters described in this invention addresses the manufacturing requirements of irregularly shaped metallized regions in 5G communication filters. Through a three-stage silver powder system, low-flow interface-bonded lead-free glass powder, fast-recovery retention lock-type carrier, and compatible preparation and application processes, it achieves a good balance between shear spreading, retention shaping, and continuous sintering conductivity in the conductive silver paste. Figures 1 to 6 As can be seen from the embodiments, comparative examples, and experimental results, the present invention can reduce sidewall sagging, thin corner silver layer, and insufficient groove filling, improve the uniformity of sintered silver layer thickness, conductivity continuity, and interface reliability, and is suitable for irregularly shaped metallized areas such as end faces, sidewalls, grooves, and through-hole edges of filters for 5G communication.
[0131] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A lead-free, environmentally friendly conductive silver paste for 5G communication filters, characterized in that, Conductive silver paste is used in the irregularly shaped metallization region of ceramic filters for 5G communication. The irregularly shaped metallization region is a metallization region with height difference, hole and groove structure or adjacent surface boundary structure. The conductive silver paste, by weight, comprises the following components: 78.0%-82.0% silver powder, 3.0%-4.8% lead-free glass powder, 13.5%-17.5% fast recovery resident lock-type carrier, 0.4%-0.9% dispersant, 0.2%-0.7% interface modifier, and 0-0.5% additives, the sum of the weight percentages of each component being 100%. The silver powder is a three-level silver powder system for film formation in irregular metallized regions, comprising 28%-42% flake silver powder, 42%-58% spherical silver powder, and 8%-18% fine-particle silver powder by total mass. The softening point of the lead-free glass powder is 485-560℃; The fast-recovery retention lock-in carrier includes a solvent, a resin film-forming agent, and a fast-recovery thixotropic component, wherein the fast-recovery thixotropic component accounts for 6%-12% of the total mass of the fast-recovery retention lock-in carrier; the fast-recovery thixotropic component includes polyamide wax and hydrophobic fumed silica, wherein the mass ratio of polyamide wax to hydrophobic fumed silica is 3:1-5:
1.
2. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 1, characterized in that, The flake silver powder has a D50 of 3.0-7.0 μm, a flake thickness of 0.10-0.25 μm, and an aspect ratio of 20-50; the spherical silver powder has a D50 of 1.2-3.2 μm; and the fine-particle silver powder has a D50 of 0.20-0.55 μm.
3. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 1, characterized in that, The lead-free glass powder has a D50 of 0.7-1.6μm, and the lead-free glass powder does not actively contain lead-containing glass components, and the lead content is less than 0.1wt%; the lead-free glass powder includes multiple components from boron oxide, silicon dioxide, zinc oxide, bismuth oxide, aluminum oxide and titanium dioxide.
4. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 1, characterized in that, The lead-free glass powder includes a first lead-free glass powder and a second lead-free glass powder, wherein the softening point of the first lead-free glass powder is lower than that of the second lead-free glass powder.
5. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 4, characterized in that, The mass ratio of the first lead-free glass powder to the second lead-free glass powder is 7:
3. The softening point of the first lead-free glass powder is 495℃, and the softening point of the second lead-free glass powder is 555℃.
6. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 1, characterized in that, The solvent is selected from one or more of terpineol, butyl carbitol acetate, and diethylene glycol butyl ether acetate; the resin film-forming agent is selected from one or more of ethyl cellulose, acrylic resin, and rosin-modified resin.
7. The lead-free, environmentally friendly conductive silver paste for 5G communication filters according to claim 6, characterized in that, The dispersant is selected from one or more of polyester dispersants, polyether dispersants, and hydroxyl-containing polymeric dispersants, and the acid value of the dispersant is less than 15 mg KOH / g. The interface modifier is selected from one or more of nano alumina, nano titanium dioxide, nano zirconium oxide, and silane coupling agent, and the average particle size of the interface modifier is 20-120 nm. The additives include at least one of leveling agents, defoamers, and anti-skinning agents.
8. A method for preparing lead-free, environmentally friendly conductive silver paste for 5G communication filters as described in any one of claims 1-7, characterized in that, Includes the following steps: S1: To prepare the basic carrier liquid, add the solvent to the reaction vessel, heat it up, add the resin film-forming agent and stir to dissolve it, cool it down and add the dispersant to obtain the basic carrier liquid; S2: Prepare the resident lock-in mother liquor. Take a portion of the base carrier liquid and add it to the mixing tank. Add the fast recovery thixotropic component and pre-disperse it. After standing and aging, the resident lock-in mother liquor is obtained. S3: Silver powder classification and pre-wetting: Add flake silver powder and spherical silver powder to a mixing tank, add some base carrier liquid and stir at low speed, then add fine-particle silver powder in batches and stir to obtain silver powder pre-dispersion paste. S4: Lead-free glass powder is dispersed in the post-dispersion stage. Lead-free glass powder and interface modifier are added to the silver powder predispersed paste and stirred to obtain silver paste premix containing glass powder. S5: Grinding and dispersing, the silver paste premix is ground in multiple passes to obtain the ground paste; S6: Low-shear mesh formation and degassing. The ground slurry is transferred to a low-speed mixing tank, and the remaining base carrier liquid, resident lock-type mother liquor and additives are added. After low-speed stirring and vacuum degassing, conductive silver paste is obtained.
9. The preparation method according to claim 8, characterized in that, In step S1, the heating temperature is 75-85℃, the cooling temperature is 45-55℃, and the dispersant is added and stirring is continued for 20-40 minutes. In step S2, the pre-dispersion speed is 900-1400 r / min, the pre-dispersion time is 20-40 minutes, the standing maturation temperature is 45-55℃, and the standing maturation time is 2-8 hours; In step S3, add 50%-65% of the base carrier liquid by mass of the base carrier liquid, stir at 200-400 r / min for 10-20 minutes, and then add fine silver powder in two batches, stirring at 400-650 r / min for 10-20 minutes after each addition. In step S4, stir at 300-500 rpm for 15-30 minutes; In step S5, the grinding is carried out sequentially using roller gaps of 45-55μm, 25-35μm, 12-18μm and 6-10μm until the scraper fineness is no greater than 10μm, and the material temperature is controlled to not exceed 45℃. In step S6, stir at 150-300 r / min for 20-40 minutes and degas under a vacuum of -0.08 MPa to -0.095 MPa for 20-40 minutes.
10. The application of a lead-free, environmentally friendly conductive silver paste for 5G communication filters as described in any one of claims 1-7, or a lead-free, environmentally friendly conductive silver paste for 5G communication filters prepared by the method described in claim 8 or 9, in the irregular metallization region of a 5G communication filter, characterized in that, This includes applying the conductive silver paste to the irregularly shaped metallized area of a ceramic filter for 5G communication by means of screen printing, scraping, pad printing or dispensing to form a wet silver layer; The irregularly shaped metallized area includes at least one of the following: end face, side wall, corner, groove, groove wall, step edge, orifice edge, through hole edge, and the junction of adjacent surfaces; The coated ceramic substrate was left to stand at 25-40℃ for 3-8 minutes to set, followed by gradient drying and sintering to obtain a sintered silver layer. The gradient drying process includes: first drying at 70-90℃ for 5-12 minutes, and then drying at 110-130℃ for 10-20 minutes; The sintering process includes: heating to 330-380℃ at 3-5℃ / min and holding for 10-20 minutes, then heating to 520-600℃ at 4-7℃ / min and holding for 5-15 minutes, and finally heating to 760-820℃ at 5-8℃ / min and holding for 8-18 minutes.
Citation Information
Patent Citations
Conductive silver paste, preparation method thereof and 5G ceramic filter
CN112037960A
Silver paste commonly used for 5G ceramic filter surface paste and hole paste and preparation and application thereof
CN114520064A
